Geochemical Assessment of Some Trace Elements in Selected Locations at Thi-Qar Governorate Soil, Southeast Iraq - Al-saad, Harith; Khwedim, Kareem; Al-khalf, Noor A. (Iraqi Journal of Science, 2023)
Trace elements (Co, Cr, Mn, Mo, Ni, Rb, Th, U, and V) in surface soil of Al-Aslah (NH1), Nasiriyah refinery (NH2), Gharraf (NH3), and Tall Al-Laham (NH4) at Thi-Qar governorate, southeast Iraq, were studied. The study aims to detect their distribution and pollution levels to reduce the subtracted from industrial sources and avoid using contaminated areas for agricultural purposes before the soil treatment process. Inductivity Coupled Plasma Mass Spectrometry (ICP-MS) technique was used to determine the concentrations of these elements, and the results showed that there is a high concentration of Cr, Ni, Mo, and Mn in the soil of the study area, which exceeded the international levels compared with other elements (Co, Th, U, and V). The Geo accumulation index (I geo) values showed that the soil area was classified as low contamination in all sites and for all trace elements except for Mo, which is polluted in Al-Gharraf and strongly polluted in Tall Al-Laham. The values of the enrichment factor (EF) were indicated to be minimal enrichment of (Mn and V) in all sites and moderate enrichment of (Co) in all sites except in the Gharraf soil sample, which is considered as minimal enrichment. At the same time, it suffers from significant enrichment of (Cr) in all sites. The values of contamination factor (CF) showed extreme contamination of Cr and Ni in all sites due to the oil industry (Nasiriyah refinery), except for Ni in the Gharraf soil sample, which is considered as high contamination and moderately contamination with Co in all sites, and low contamination with Mn and V. The main cause of the increasing trace element concentrations in the study area that the samples located in industrial sites where trace elements are one of the waste products from fuel combustion from the oil fields and the waste of the brick factories near the study area, also the nature of the study area soil which is clay soil that absorb the trace elements on its surfaces.